Research on Global Bicycle Market and Development Trend - Wang Yang Michael (SHS Web of Conferences)
In the past decades, the global bicycle market has experienced great changes and development. This is partly due to increased awareness of the environment and traffic jams. Furthermore, the demand for bicycles surged during the COVID-19 pandemic since people starts to care more about their health. Therefore, there exists great prospect and importance to carry out in detailed research about the bicycle market. However, current research about the bicycle market focus only on certain segment or part of the area. By studying market data and examining brand and regional difference, this article aims to find the key factors that drives the industry, and therefore make recommendations for enterprises. This article will discuss the development status and future trends of global bicycle market. It analyses technological advancements, market competition, and regional difference over the world. The result shows that global bicycle market has a great prospect and makes several recommendations to bicycle companies. Bicycle companies should invest in new technologies, expand sales channel, focus on market segmentation, and establish strong brand influence.